2019
DOI: 10.1186/s12871-019-0681-2
|View full text |Cite
|
Sign up to set email alerts
|

Hemopexin alleviates cognitive dysfunction after focal cerebral ischemia-reperfusion injury in rats

Abstract: BackgroundIschemia-reperfusion (I/R) is a critical pathophysiological basis of cognitive dysfunction caused by ischemia stroke. Heme-oxygenase-1 (HO-1) is the rate-limiting enzyme for the elimination of excessive free heme by combining with hemopexin (HPX), a plasma protein that contributes to eliminating excessive free heme during ischemia stroke. This study aimed to elucidate whether HPX could alleviate cognitive dysfunction in rats subjected to cerebral I/R.MethodsRats were randomly divided into five groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 26 publications
(16 reference statements)
0
23
0
Order By: Relevance
“…Therefore, Hpx could potentially be applied as a human blood-derived product similar to other plasma proteins, such as albumin, α1-antitrypsin or immunoglobulins, which are well-established therapies (34). Hpx has already been tested in numerous animal models and showed beneficial effect in most of the tested parameters [ (10,13,14,19,20,23,29,33,(35)(36)(37)(38)(39)(40)(41); Table 2].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Hpx could potentially be applied as a human blood-derived product similar to other plasma proteins, such as albumin, α1-antitrypsin or immunoglobulins, which are well-established therapies (34). Hpx has already been tested in numerous animal models and showed beneficial effect in most of the tested parameters [ (10,13,14,19,20,23,29,33,(35)(36)(37)(38)(39)(40)(41); Table 2].…”
Section: Discussionmentioning
confidence: 99%
“…Based on its lipophilic nature, heme may induce lipid peroxidation and subsequent membrane injury, which finally results in apoptosis. Indeed, scavenging of heme by intracerebroventricularly applied hemopexin reduced the infarct volumes, improved neurological function and cognitive function after focal ischemia (62,63). We therefore think that the decreased HO activity, which is caused by CA, results in neuronal deficits.…”
Section: Discussionmentioning
confidence: 96%
“…This protective effect was also linked to HO1 activity because it was reversed by the HO1 inhibitor, zinc-PPIX [119]. In a similar experimental approach, HPX was protective after cerebral ischemia/reperfusion injury and protection was lost when zinc-PPIX was given [119].…”
Section: Hemopexin Protects the Blood-brain Barriermentioning
confidence: 98%
“…Using a model of cerebral ischemia-reperfusion injury in rats, focal cerebral ischemic and reperfusion, Dong and colleagues [119] showed that HPX alleviated cognitive dysfunction rapidly when injected intracerebro-ventricularly once reperfusion was initiated. This protective effect was also linked to HO1 activity because it was reversed by the HO1 inhibitor, zinc-PPIX [119]. In a similar experimental approach, HPX was protective after cerebral ischemia/reperfusion injury and protection was lost when zinc-PPIX was given [119].…”
Section: Hemopexin Protects the Blood-brain Barriermentioning
confidence: 99%